The impact of financial inclusion on economic growth in developing countries - Saha, Sumanta Kumar; Qin, Jie; Inaba, Kazuo (Journal of Accounting, Business and Finance Research, 2023)
This study analyzes the impact of financial inclusion on economic growth in 104 developing countries from 2004–2019. We construct a novel composite financial inclusion index and apply the dynamic panel estimation technique to examine the impact of financial inclusion. The results indicate that financial inclusion positively correlates with economic growth in developing countries but not in high-income countries. This study shows that financial inclusion affects economic growth primarily by expanding opportunities for lower-income people. With increased financial access, those in the lower-income bracket can expand their economic activity, which results in economic growth in developing countries. In high-income countries, access to financial services is already high, and financial inclusion may not offer new opportunities to a larger segment of the population. The study also compares financial inclusion and financial development. The results suggest that financial inclusion contributes to financial development in developing countries by enhancing access to financial services. The findings recommend that policymakers in developing countries may use financial inclusion to increase economic growth.